(3efXheI aj GdQVGYs - (3GdfLaj, , GdCYSe, GdCYSe, eMeO Ydj Hf MSjf Hf eMeO, J (B1233(3g` (B1817(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg Ydi CaVGdg (B*** (3HGdQRb ddWad dOi GSJgdGdg (B.... (3UM GdMOjK Yf fHj GdCeI (B*** (3hYf Hfjg GdSGOI GdCFeI (B*** (3Cf GdQVGY Mceg Mce GdfSH (B*** (3ajeG dg Mce JMQje hLHs
(3BNQgG (B:s
(3BNQgG(B: (3hjcQg GSJQVGY ef Yf GdRfG (B*** (3bO hdOJ hGdShA SjA GdLfG (B*** (3dcf CJi ajgG MOjK Ef ef (B*** (3CMdgG Gdehdi abO WGH GddHf (B*** (3Ke fUd HYO PGd GdebGd (B*** (3Ydi GdfHj GdeUWai hGdBd(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 297s
(3GdPQjYI, L (B23: 69s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis